ANALISIS TRANSAKSI DIGITAL NON FUNGIBLE TOKEN (NFT), SEBAGAI INSTRUMEN INVESTASI DAN JUAL BELI ASET VIRTUAL MENURUT PERSPEKTIF EKONOMI ISLAM (Studi Transaksi Digital Virtual Asset NFT pada Platform OpenSea.io) - Siti Saroh; Listian Indriyani Achmad; Muhammad Hamdan 'Ainulyaqin; Sarwo Edy (ITB AAS INDONESIA Surakarta, 2023)
This study aims to find out and analyze how Islamic economics views buying and selling transactions and investments in Non-Fungible Token (NFT) virtual assets. This type of qualitative research with a phenomenological approach. The data source is obtained from the OpenSea platform. The results of this study indicate that digital transactions for buying and selling and investment purposes are permissible in Islam. By considering the halal elements of each transaction object. Regarding Non-Fungible Token (NFT) digital transactions are not legal in Islam because the transactions use cryptocurrencies. In the MUI Fatwa, the use of cryptocurrencies as currency is illegal and contrary to Law number 7 of 2011 and Bank Indonesia Regulation number 17 of 2015.